Sustained in vitro root development obtained in Pinus pinea inoculated with ectomycorrhizal fungi. - Oliveira, Paulo (2003)
Stone pine (Pinus pinea L.) is an economically important forest tree in Mediterranean climates and has been the target for selection efforts through micropropagation. Previous attempts on microshoots, derived from mature seed cotyledons, reached incipient rooting after induction with a combination of auxin and hypertonic shock, but their development in vitro was not sustained. At this stage, co-culturing plantlets with some fungi isolated from ectomycorrhizas succeeded in overcoming this barrier, enabling satisfactory development in vermiculite and later in soil. About half of the fungal isolates tested helped the plants resume root growth. Although control plants (in the absence of fungi) developed roots at a later stage, i.e. during the post-transplanting acclimation in vermiculite, their growth was weaker. The root systems of some inoculated plants had ectomycorrhizas from the introduced fungi being carried over when the plants were transferred from the co-cultures to vermiculite. In conclusion, co-culturing rooted microshoots with ectomycorrhizal fungi can be an effective means to overcome the difficulties encountered in the use of micropropagation methods on this species.